Apakah Ada "Anak Allah" dalam Markus 1:1? Sebuah Pesan Tidak Biasa dari Anak Allah - Wu, Calvin (Verbum Christi: Jurnal Teologi Reformed Injili, 2025)
There has been debate over the phrase “υἱοῦ τοũ θεοῦ” (Son of God) in Mark 1:1, which some textual critics believe is not original and was added later (known as the shorter reading). Conversely, other textual critics still argue that this phrase is original (known as the longer reading). This study will demonstrate that the presence of the phrase υἱοῦ τοũ θεοῦ in Mark 1:1 is justified. Considering external evidence, I find that although various witnesses support both the shorter and the longer readings and are evenly distributed across ancient manuscripts, examining the genealogical relationship provides strong evidence for the phrase’s existence. The omission of υἱοῦ τοũ θεοῦ in some majuscules should be understood as a homoioteleuton error made by scribes. Additionally, internal evidence also strongly supports the phrase’s presence, as seen in the frequent use of this phrase, which is closely related to the Messianic Secret and inclusio. This evidence leads to the firm conclusion that the phrase υἱοῦ τοũ θεοῦ truly appears in Mark 1:1. The inclusion of this phrase at the start of Mark’s Gospel conveys an extraordinary message that contrasts sharply with what first-century readers in Judaism, Hellenism, and the Roman Empire would have expected.